Are employees well evaluated in their CSR actions? The perception of managers in an emerging country - Lizarzaburu Bolaños, Edmundo (2020)
Purpose – This paper tests the influence of employees’ involvement in CSR activities on managers’ perceptions regarding business confidence. Design/methodology/approach – A quantitative methodology was used to contrast the hypotheses presented in this paper. The empirical research began in March 2016. In April 2016, a questionnaire was sent by email to the 1,745 managers of the multiple banks with a message explaining the relevance of the research. The data gathering process finished in July 2016. Findings – The causal model proved the influence of the perception of employees’ involvement in the CSR actions of Peruvian banks in terms of improving the perception of business confidence by managers. The relationship found was not statistically significant at a level of p<0.05. Therefore, the assessment of the involvement of workers in CSR in Peruvian banks does not significantly influence business confidence. Originality/value – The main contribution of this paper is that it empirically analyzes how business confidence is perceived by managers and how it is influenced by perceptions of employees’ involvement in CSR actions in a context barely investigated: an emerging country.